Evaluation of photocatalytic activity of copper ferrite nanoparticles - Priya, R.; Stanly, S.; Anuradha, R.; Sagadevan, Suresh (IOP Publishing, 2019)
The research expresses a simple green genesis approach to synthesize copper ferrite (Cu2Fe2O4) nanoparticles using copper sulphate (CuSO4) along with ferrous sulphate (FeSO4). The investigation has been made to do photocatalytic decolourization of Methylene Blue dye under UV light utilizing copper ferrite. The photocatalyst was prepared from fruit peel waste such as Pomegranate, Apple, Grapes, Orange and Banana (PAGOB). The characterization of nanoparticles was done by X-ray diffraction (XRD) as well as Scanning Electron Microscope (SEM). The photodegradation rate of the dye was examined spectrophotometrically. The reaction was observed for pH, dye concentration, a dose of photocatalyst and intensity of light on the rate of photocatalytic to know the effect. Finally, the result was that the photodegradation has touched 88% under ideal conditions. © 2019 IOP Publishing Ltd.